The impact of Prophet Muhammad motivation Techniques on students’ performance - Wan Yusoff, Wan Mazwati (Elsevier, 2012)
Research from Islamic perspective should begin from the truth of the Qur’an and Sunnah (Acikgenj, 1996), the main source of Islamic knowledge. From the analysis of the main sources of Islamic knowledge, theories are formulated and tested. We embark on this research to formulate techniques used by Prophet Muhammad to motivate students to perform better. This study attempts to extract techniques used by The Prophet in raising his companions’ self-esteem and motivation to change negative behavior thus perform better; and to explore and describe the impacts of these techniques on students’ performance. This study employed qualitative research method.